Physical activity interests and preferences of cancer patients with brain metastases: a cross-sectional survey. Issue 1 (December 2016) - Lowe, Sonya; Danielson, Brita; Beaumont, Crystal; Watanabe, Sharon; Courneya, Kerry
Abstract Background Physical activity has been shown to positively impact cancer-related fatigue, physical functioning and quality of life outcomes in early stage cancer patients, however its role at the end stage of cancer has yet to be determined. Brain metastases are amongst the most common neurological complications of advanced cancer, with significant deterioration in fatigue and quality of life. The purpose of the present study was to examine the physical activity interests and preferences of cancer patients with brain metastases initiating palliative whole brain radiotherapy. Methods Thirty-one patients aged 18 years or older, cognitively intact, diagnosed with brain metastases, and with Palliative Performance Scale scores of greater than 30 %, were recruited from a multidisciplinary outpatient brain metastases clinic. An interviewer-administered survey was used to assess physical activity interests and preferences of participants who were embarking upon palliative whole brain radiotherapy. Results 87 % (n  = 27) of participants felt that physical activity was important, however there was limited interest in participating in a structured program at the onset of palliative whole brain radiotherapy. Lung cancer diagnosis was associated with being less interested in participating in a physical activity program, and feeling less able to participate in a physical activity program at the onset of palliative whole brain radiotherapy. Conclusions Cancer patients with brain metastases demonstrate limited interest and varied preferences for physical activity during palliative whole brain radiotherapy. Additional pilot work with this patient population is needed before physical activity interventions can be tested in clinical research.